Clinical and anamnestic predictors of poor long-term prognosis in patients with chronic heart failure and implanted cardioverter-defibrillator - Nataliya B. Lebedeva; Ilias V. Talibullin; Pavel G. Parfenov; Olga L. Barbarash (Терапевтический архив)
Aim. Identification of a complex of clinical and anamnestic predictors of an unfavorable long-term prognosis in patients with heart failure with low left ventricular ejection fraction and an implanted cardioverter-defibrillator (ICD).